Intervention programmes and policies for maternal mortality reduction in Zanfara State, Northwest, Nigeria: a review 2005-2015 - Mohammed Maiwada, Abdullahi; A.Rahman, Nor Azlina; Abdul Rahman, Suzanah; Mamat, Nik Mazlan; Baba, Tukur (The International Institute for Policy Review & Development Strategies (IIPRDS), 2015)
Estimates indicate that Nigeria has more than 50,000 maternal deaths annually, while many key maternal health indicators have remained stagnant or have worsened over the last decade, and coverage and utilization of key interventions are correspondingly low. The maternal mortality in Nigeria is 576 per 100,000 live births according to Nigeria demographic health survey 2013.This study used both quantitative and qualitative methods as well as secondary data to review the interventions program and policies for the reduction of maternal mortality in Zamfara state. The results indicated that socio-cultural issues, non-utilization of health facilities and preference for home deliveries by mothers remain some of the major reasons for the high maternal deaths. Other institutional factors include insufficient manpower and frontline health care workers. There are obvious gaps in policies, funding and political commitment, poverty, weakened capacity of public institutions, low literacy levels and other entrenched negative health seeking behaviours.